Factors Related to Negative Emotions among the Destitute at a Public Protection Center - Kotcharit, Fareeda; Intaput, Pichamon; Vatanasin, Duangjai (Thai Red Cross Nursing Journal, 2024)
This correlational descriptive research aimed to examine the level of negative emotions, along with factors related to negative emotions, among the destitute at a public protection center. A sample of 100 participants was selected using simple random sampling from a group of destitute men and women at a public protection center. The research instruments involved a personal information form, the Depression Anxiety Stress Scales - 21 scale (DASS-21), the WHO quality of life - brief Thai version (WHOQOL-BREF-THAI) scale, an optimism scale, a resilience scale, and a social support scale. The data were collected from October to December, 2021. Data were analyzed using descriptive statistics and Pearson’s product moment correlation coefficient. The results revealed that 57 percent of participants were men and 43 percent were women. The participants had an average age of 51.43 years (SD = 14.69). 52.50 percentage of the participants entered the public protection center due to family problems. The sample experienced a mild level of negative emotions (Mean = 13.78, SD = 8.66). Furthermore, the results indicated that social support, quality of life, optimism (r = -.209, -.219, -.225, p < 0.5 respectively), and resilience (r =-.282, p < .01) were significantly negatively correlated with negative emotion. This research findings suggest that nurses, mental health care providers, and staff at public protection centers should be aware of the continuous negative emotions participants face in order to observe emotional changes that may affect those at the center. Additionally, they should provide early intervention to care and provide social support to this group.